The Idea of Civilization and the Making of the Global Order - Linklater, Andrew (Book collections on Project MUSE., 2021)
The idea of civilization recurs frequently in reflections on international politics. However, International Relations academic writings on civilization have failed to acknowledge the major 20th-century analysis that examined the processes through which Europeans came to regard themselves as uniquely civilized -- Norbert Elias's On the Process of Civilization. This book provides a comprehensive exploration of the significance of Elias's reflections on civilization for International Relations. It explains the working principles of an Eliasian, or process-sociological, approach to civilization and the global order and demonstrates how the interdependencies between state-formation, colonialism and an emergent international society shaped the European "civilizing process".--